Association between breast cancer and thyroid cancer risk: a two-sample Mendelian randomization study - Tan, Hong; Wang, Sisi; Huang, Feifei; Tong, Zhongyi (Frontiers in Endocrinology, 2023)
The risk of breast and thyroid cancer is increasing, but it is unclear whether this association is driven by heightened medical surveillance or underlying etiological factors. Observational studies are vulnerable to potential biases such as residual confounding and reverse causation, which can compromise causal inference. To address these limitations, we conducted a two-sample Mendelian randomization (MR) analysis to investigate the causal relationship between breast cancer and increased risk of thyroid cancer. Methods: The single nucleotide polymorphisms (SNPs) associated with breast cancer were obtained from a genome-wide association study (GWAS) in Breast Cancer Association Consortium (BCAC). The latest and largest accessible GWAS from the FinnGen consortium provided thyroid cancer data at the summary level. Four MR analyses, including the inverse-variance-weighted (IVW), weighted median, MR-Egger regression, and weighted mode, were performed to evaluate the potential causal connection between genetically predicted breast cancer and higher risk for thyroid cancer. We also used sensitivity analysis, heterogeneity and pleiotropy tests to ensure the reliability of our findings. Results: There was a causal relationship between genetically predicted breast cancer and thyroid cancer (by the IVW method, odds ratio (OR) = 1.135, 95% confidence interval (CI): 1.006 to 1.279, P = 0.038). However, there was no causal association between genetically predicted triple-negative breast cancer and thyroid cancer (by the IVW method, OR = 0.817, 95% CI: 0.610 to 1.095, P = 0.177). There was no directional pleiotropy or horizontal pleiotropy in this study. Conclusion: This two-sample MR study provided a causal relationship between ER-positive breast cancer and increased risk of thyroid cancer. Our analysis did not reveal a direct correlation between triple-negative breast cancer and thyroid cancer.